2007
DOI: 10.1002/crat.200711014
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the crucible bottom shape on the heat transport and fluid flow during the seeding process of oxide Czochralski crystal growth

Abstract: For the seeding process of oxide Czochralski crystal growth, influence of the crucible bottom shape on the heat generation, temperature and flow field of the system and the seed-melt interface shape have been studied numerically using the finite element method. The configuration usually used in a real Czochralski crystal growth process consists of a crucible, active afterheater, induction coil with two parts, insulation, melt, gas and seed crystal. At first, the volumetric distribution of heat inside the metal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 5 publications
1
14
0
Order By: Relevance
“…Anselmo A P et al [14] and Tavakoli M H et al [15] showed that a cylindrical crucible with a curved bottom has advantages for crystallization. Therefore, it is proposed recently by Mokhtari F et al [16,17,18] to modify the device as a cylindro-spherical system (figure 1).…”
Section: Modellingmentioning
confidence: 99%
“…Anselmo A P et al [14] and Tavakoli M H et al [15] showed that a cylindrical crucible with a curved bottom has advantages for crystallization. Therefore, it is proposed recently by Mokhtari F et al [16,17,18] to modify the device as a cylindro-spherical system (figure 1).…”
Section: Modellingmentioning
confidence: 99%
“…From the 80s until the mid-90s, Kobayashi [1], Derby [2][3][4] and Tsukada [5] successfully applied two-dimensional numerical analysis to compute the temperature distribution, the flow field and the melt-gas interface in a CZ system. However, recent studies performed by Tsukada [6][7], Imaishi [8][9], Wilke [10][11], Banerjee [12] and Tavakoli [13][14][15] have shown that specific global, three-dimensional and unsteady features of the melt flow can make a significant contribution to the heat and mass transfer near the melt-crystal interface, and may even govern the formation of the crystallization front for large-diameter crystal growth. Induction heating is frequently used in the CZ crystal growth process.…”
Section: Introductionmentioning
confidence: 97%
“…Tavakoli and Wilke [13][14][15] conducted a series of numerical simulation studies of CZ sapphire crystal growth. First, they performed a two-dimensional numerical simulation of heat generation and heat transport in a real Czochralski system without any crystal and melt, to investigate the effect of the insulation and the gap between the crucible and the afterheater on the air flow and temperature field.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly, the crucible bottom shape can influence the fluid flow and heat transfer process during the seeding. A computer modeling [13] shows that a crucible with the round corners at the bottom has several differences with a flat bottom crucible, such as increasing the velocity of melt flow, thermal convection and ____________________ lifting the melt's maximum temperature upward. However, no experimental investigation has been reported in this study to verify these theoretical findings.…”
Section: Introductionmentioning
confidence: 99%